The Influence of the Shopee Flash Sale Program on Impulsive Purchase Decisions of Students - Aulya, Diva (International Journal Administration, Business & Organization, 2022)
One example of digitalization of technology is the creation of e-commerce in the business sector. E-commerce Shopee does one of these strategies to retain its customers by holding a flash sale program. Limited time and product quantity during flash sales raise several opportunities for consumers to make unplanned purchases or also known as impulsive buying behavior. Therefore, this study aims to determine whether or not the flash sale program has an effect on the impulse purchase decision of Shopee's impulsive consumers. The research was conducted using a quantitative descriptive method with data collection using a questionnaire. The total number of respondents was 120 Bandung State Polytechnic students who are Shopee consumers. Data analysis was conducted using SPSS 25 software. This study tested validity, reliability, normality, and simple linear regression analysis. From the results of the analysis obtained, it can be stated that flash sales have a positive effect on impulsive student buying decisions by 70.8%.